2011
DOI: 10.1118/1.3602459
|View full text |Cite
|
Sign up to set email alerts
|

Iodine kinetics and dosimetry in the salivary glands during repeated courses of radioiodine therapy for thyroid cancer

Abstract: The iodine uptake of salivary glands is continuously reduced during the courses of therapy. The phenomenon of hyper-radiosensitivity may to some extent account for the occurrence of salivary gland hypofunction at very low radiation doses with low dose rates in (131)I therapy. On the other hand, failure to incorporate a nonuniform and preferential uptake by salivary gland ductal cells may result in underestimating the actual dose for the critical tissue. Other methods, including (124)I voxel-based dosimetry, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…This may be associated with the reduction in uptake ability and hence the total amount of absorbed radioactivity over successive courses of treatment. Liu et al [28] recently reported that the maximum uptake of I-131 by the parotid and submandibular glands typically occurs 2-4 h after oral administration. The maximum uptake activity per kilogram of gland tissue reduces with the increasing cumulative dose of I-131 (because of a reduction in overall function).…”
Section: Discussionmentioning
confidence: 98%
“…This may be associated with the reduction in uptake ability and hence the total amount of absorbed radioactivity over successive courses of treatment. Liu et al [28] recently reported that the maximum uptake of I-131 by the parotid and submandibular glands typically occurs 2-4 h after oral administration. The maximum uptake activity per kilogram of gland tissue reduces with the increasing cumulative dose of I-131 (because of a reduction in overall function).…”
Section: Discussionmentioning
confidence: 98%
“…After dead-time, scatter, and Buijs background corrections (23), the geometric mean value of the anterior and posterior counts in each region of interest was recorded. Attenuation correction was applied by using the data from the computed tomographic study (Brilliance; Philips) performed after 131 I administration and a uniform linear attenuation coefficient of 0.11 cm 21 for 131 I (19). The attenuation-corrected counts were converted to activity values by using the scintillation camera detection efficiency as measured with the calibration sources.…”
Section: Implication For Patient Carementioning
confidence: 99%
“…The standard consisted of a 10-mL vial filled with a radioactive liquid of 131 I and stored in the acrylic block. A full description of the dosimetry theory and the corrections of the imaging data has been published previously (19,20).…”
Section: Implication For Patient Carementioning
confidence: 99%
“…An objective assessment of the salivary gland RAIinduced injury may be enabled by dosimetry. Recent dosimetric studies using either 131 I-NaI planar scans and salivary gland CT (used for salivary gland volume determination) or 124 I-NaI PET/CT proved that average salivary gland dose per commonly administered RAI ablation activity is about one order of magnitude lower than the external beam radiotherapy dose necessary to induce salivary gland radiation injury 17,18 . Nevertheless, continuously decreasing RAI uptake in salivary glands (marker of parenchymal integrity) during the repeated RAI administrations has been observed 18 .…”
Section: Introductionmentioning
confidence: 99%